The Use of Attribution Theory in Accounting Research: a Literature Review - Azmi, Zul; Nikmah, Khoirotun (Equity: Jurnal Akuntansi, 2025)
This research aims to determine the development of accounting and management research that uses attribution theory as its theoretical basis, which was observed from 2015-2022. Bibliometric reviews are used to map the use of attribution theory in accounting research to find out how many citations from journals have been found. Based on search results on the Scopus and Sinta2 Ministry of Education and Culture websites, 9 Scopus-indexed articles and 11 Sinta2-accredited articles related to attribution theory were obtained. The results show that relatively little use of attribution theory is made as a basis for research in the field of accounting. Accounting research published in journals indexed by Sinta2 relatively uses attribution theory to explain auditing, taxation, and management accounting phenomena. However, relatively few were found to explicitly express the use of attribution theory to explain phenomena in accounting research in Scopus-indexed journals.